Synthesis of mesoporous silica for adsorption of chlordiazepoxide and its determination by HPLC: Experimental design. Issue 20 (10th September 2019) - Momtazan, Fatemeh; Khodadoust, Saeid; Zeraatpisheh, Fatemeh; Behbahani, Mohammad
Abstract: In this work, mesoporous silica (SBA‐15‐NH2 ) was used as an efficient adsorbent for extraction of chlordiazepoxide from different samples based on dispersive nanomaterial‐ultrasound assisted microextraction followed by high‐performance liquid chromatography. The prepared sorbent was characterized by fourier transform infrared spectroscopy, scanning electron microscopy, low‐angle X‐ray diffraction, thermal analysis, and N2 adsorption‐desorption surface area measurement. Several variables affecting the extraction efficiency of the chlordiazepoxide, including the amounts of adsorbent, time of adsorption, pH and volume of desorption solvent were optimized by central composite design combined with desirability function. The values of variables were set as 10 mg of SBA‐15‐NH2, 15 min adsorption time, pH = 7.3 and 1 mL methanol. The linear response (0.998) was obtained in the range of 0.006–10 µgmL −1 with detection limit 0.0014 µg/mL and extraction recovery was in the range of 91–96% with relative standard deviation < 6%.